CONTINUITY OF ISLAMIC LAW AND CULTURE: THE IMPLEMENTATION OF THE PRINCIPLE OF AL-'ADAH AL-MUHAKKAMAH IN THE SIRI’ NA PACCE PHILOSOPHY OF THE BUGIS-MAKASSAR COMMUNITY - Suandi; Tarmizi; lukman ansar; Kasmanita (Jurnal Ar-Risalah, 2026)
The flexibility of Islamic law in responding to the dynamics of social life can be achieved through the concept of ‘urf, or customary practice. This study aims to analyze the continuity of Islamic law and community culture regarding the implementation of the principle of al-‘adah al-muhakkamah in relation to the philosophy of Siri’ na Pace, which represents the local wisdom of the Bugis-Makassar people in South Sulawesi. This research is a literature review employing a qualitative method with normative and sociological approaches. Data analysis was conducted using descriptive qualitative methods by integrating normative Islamic legal texts with the values alive in society (Siri’ na Pacce). The results indicate that the principle of al-‘adah al-muhakkamah remains a robust method for formulating Islamic law responsive to societal dynamics, provided that such cultural practices do not conflict with Islamic sharia. Its implementation within the philosophy of Siri’ na Pacce (a sense of shame and empathy), deeply rooted in Bugis-Makassar society, extends beyond mere values; it serves as a guiding principle for life that prioritizes honesty, responsibility, and social solidarity. This philosophy can be harmonized with Islamic law as a foundation for resolving issues such as silariang or passampo siri’ cases, provided that the values it contains align with the principles of maqashid al-shari’ah. This study concludes that the synergy between Islamic law and local wisdom, through the principle of al-‘adah al-muhakkamah, can establish a legal framework that is dynamic, responsive, fair, and grounded in local wisdom.